Bridging nutrition and neurology: malnutrition's role in perioperative neurocognitive disorders - Luo, Li; Gong, Qihai; He, Miao; Zhu, Yuhang; Yu, Wanqiu; Gong, Taowu; Zhao, Pengcheng; Zhu, Zhaoqiong (Frontiers in Nutrition, 2025)
This literature review examines the relationship between malnutrition and perioperative neurocognitive disorders (PND), which encompass cognitive impairments occurring throughout the perioperative period, including pre-existing cognitive impairments, postoperative delirium, delayed neurocognitive recovery, and postoperative cognitive dysfunction. Malnutrition is associated with an increased incidence of PND, affecting patient recovery and quality of life. Studies suggest that preoperative malnutrition may heighten the risk of PND, and that preoperative nutritional diagnosis and perioperative nutritional interventions could reduce the occurrence of PND. The review discusses the definition, diagnosis, and indicators of malnutrition, as well as the mechanisms by which malnutrition leads to PND, including direct pathways such as psychological factors, abnormal neurotransmitter synthesis, and changes in brain structure and function, and indirect pathways like impaired immune function, neuroinflammation, mitochondrial dysfunction, intestinal barrier damage, disruption of the gut-brain axis, lymphatic system dysfunction, and endocrine disruption. Finally, this paper summarizes the existing nutritional intervention strategies for improving PND, explores the research directions of malnutrition and PND, and emphasizes that future research needs to clarify the role of nutritional intervention in specific populations and conduct in-depth studies on the molecular mechanisms of nutritional intervention and PND prevention.